2014
DOI: 10.5114/hpr.2015.47623
|View full text |Cite
|
Sign up to set email alerts
|

Development of physical competence through motor skill acquisition for children and youth with disabilities: Parental perceptions

Abstract: health psychology report • volume 3(1), 5 original article background Parents are integral social agents in children's physical activity choices and involvement providing direct (feedback) and indirect (providing opportunities) competence information as well as multiple levels of support for activity engagement. Research is scant on parent perceptions and/or expectations specific to physical competencies and activity experiences among children with disabilities. The objective of this study was to capture pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Typically, behavioral intervention studies have demonstrated that children with ASD rely heavily on parents and caregivers to model effective strategies for behavior and emotion regulation [ 13 ]. Unfortunately, when it comes to FMS, parents of children with ASD may lack the knowledge or skills to be able to effectively teach or engage their children in these types of activities [ 14 , 15 ]. Early intervention programs tend to include parents as part of the intervention, but these programs typically focus on improving communication skills with minimal attention to the improvement in FMS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, behavioral intervention studies have demonstrated that children with ASD rely heavily on parents and caregivers to model effective strategies for behavior and emotion regulation [ 13 ]. Unfortunately, when it comes to FMS, parents of children with ASD may lack the knowledge or skills to be able to effectively teach or engage their children in these types of activities [ 14 , 15 ]. Early intervention programs tend to include parents as part of the intervention, but these programs typically focus on improving communication skills with minimal attention to the improvement in FMS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that parental support may be a facilitator for FMS, yet how parents can be involved in such interventions is not clear. Despite the benefits of FMS acquisition for children with ASD, interventions addressing the FMS of children with ASD, particularly parents as facilitators, are scarce [ 5 , 14 ]. Feasibility studies are used to understand the effectiveness of parent-mediated FMS interventions and highlight the intervention elements that contribute to FMS’s improvement in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the absence of previous indicators during the first 3 years of a child´s development is one of the main reasons for the perception error. In this regard, it has been found that the parents achieve improved perception levels for disorders which have been previously diagnosed, and also when they take part in intervention programs (Hurley and Burt, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Teenagers with disabled siblings were characterized by lower physical activity and worse psychological wellbeing than siblings of healthy children, even though children who had a disabled sibling were not themselves less physically able than those who had only healthy siblings (Cȩlik et al, 2018). Hurley et al, 2018 investigated the role of parents/caregivers in the willingness of children with disabilities to take up physical activity. Parents indicate increased demand for services related to physical activities involving social interactions, which could benefit the social interactions of both their disabled children and themselves.…”
Section: Physical Activity and The Role Of The Family Environment Of A Child With Disabilitymentioning
confidence: 99%
“…They reported challenges and stress factors associated with insufficient support or education in terms of the ability to organize physical activity outside of school. They studied children with disabilities from the autism spectrum, down syndrome, and developmental disabilities, which are not assessed in this review, however Hurley et al, 2018 emphasize the importance of the role of caregivers in initiating physical activity. Parents/caregivers are usually integral social factors in children choosing and engaging in physical activity and are the main source of information about children's motor and social competences.…”
Section: Physical Activity and The Role Of The Family Environment Of A Child With Disabilitymentioning
confidence: 99%